Artistic practical activities in art education (Palíndromo, 2021)
Everyone agrees to put practical activities at the heart of artistic teaching. Whether or not there isan “artistic”, “aesthetic” or “poetic” dimension is a question that haunts these teachings. How can we be sure that artistic dimension is present, in particular during practical workshop activities? Since the early of the 19th century, democratization of arts has been the main aim of practicalartistic education, the artistic dimension is ensured by the development of creative imaginationand its support from artistic circles, just like our contemporary teachings. This article proposes to describe the place given to the artistic dimension in practical activities, by French and Quebec plastic arts programs at elementary and secondary levels and more generally in the teachingof drawing in the 19th and 20th centuries. Noting the limits of French-speaking practices and research with regard to practical artistic activities, we conclude with the presentation of research examples to develop a didactic of practical artistic activities, which seems essential to us, to whatwe could call an aesthetic experiential culture.